Change Management In Improving The Quality And Competitiveness Of Islamic Boarding Schools - Mustajib; Prim Masrokan Mutohar; Akhyak; Abd. Aziz (Pondok pesantren As-salafiyah As-Safi'iyyah, 2025)
Pesantren, as the oldest Islamic educational institution in Indonesia, faces the challenges of modernization and globalization that demand improvement in quality and competitiveness. This research aims to analyze change management at Pondok Pesantren Tahfidhil Qur’an Sirojul ’Ulum Semanding Tertek Pare and Pondok Pesantren Darussalam Sumbersari Kencong Kepung in order to enhance quality and competitiveness. The research employs a qualitative approach with a multisite design. Data was obtained through in-depth interviews, participatory observation, and documentation studies, and then analyzed using the interactive model by Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results show that change management in both pesantren encompasses four dimensions. First, visionary change policies: Sirojul 'Ulum integrates tahfidz education with formal institutions, while Darussalam implements a mu'adalah system and strengthens da'wah. Second, the implementation of changes is carried out participatively through curriculum innovation, learning methods, and community-based da'wah programs. Third, change control is managed through monitoring mechanisms, evaluation, as well as the use of technology and pesantren regulations. Fourth, improvement actions are conducted continuously through curriculum refinement, enhancement of teacher competencies, strengthening the economics of pesantren, and a more adaptive disciplinary approach. This study concludes that effective pesantren change management must integrate visionary policies, participatory implementation, technology and culture-based control, and continuous improvement actions. These findings have theoretical implications in the development of Islamic education management literature, as well as practical implications for pesantren managers and policymakers in supporting quality and competitive pesantren transformation.